Trace elements concentrations in soil, desert-adapted and non-desert plants in central Iran: Spatial patterns and uncertainty analysis. (December 2018) - Sakizadeh, Mohamad; Rodríguez Martín, Jose Antonio; Zhang, Chaosheng; Sharafabadi, Fatemeh Mehrabi; Ghorbani, Hadi
Abstract: The concentrations of Cd, Cr and Pb in soil samples and As, Cd, Cr and Pb in plant specimens were analyzed in an arid area in central Iran. Plants were categorized into desert-adapted ( Haloxylon ammodendron, Atraphaxis spinosa and Artemisia persica ) and non-desert species. It was found that the trace element (TE) accumulating potential of the desert species ( Haloxylon ammodendron and Artemisia persica ) with a mean value of 0.1 mg kg −1 for Cd was significantly higher than that of the majority of the non-desert species with an average of 0.05 mg kg −1 . Artemisia also had a high As accumulating capability with a mean level of 0.8 mg kg −1 in comparison with an average of 0.2 mg kg −1 for most of the other plant species. The mean values of Cr and Pb in Haloxylon ammodendron and Artemisia persica were 5 and 3 mg kg −1, respectively. Among the desert-adapted plants, Atraphaxis proved to be a species with high Cr and Pb accumulating potential, as well. The geoaccumulation index and the overall pollution scores indicated that the highest environmental risk was related to Cd. Different statistical analyses were used to study the spatial patterns of soil Cd and their connections with pollution sources. The variogram was estimated using a classical approach (weighted least squares) and was compared with that of the posterior summaries that resulted from the Bayesian technique, which lay within the 95% Bayesian credible quantile intervals (BIC) of posterior parameter distributions. The prediction of cadmium values at un-sampled locations was implemented by multi-Gaussian kriging and sequential Gaussian simulation methods. The prediction maps showed that the region most contaminated by Cd was the north-eastern part of the study area, which was linked to mining activities, while agricultural influence contributed less in this respect. Graphical abstract: Image 1 Highlights: Trace element accumulating potential of desert plants was high. Haloxylon, Atraphaxis and Artemisia genera are potential candidates for phytoremediation. Mine sites significantly contributed toward detected values of cadmium. Generated maps of cadmium produced by SGS were more reliable that multi-Gaussian kriging method.